Mapping of Developmental Stages in Graduate Learning Outcomes in the Islamic Religious Education Curriculum - Uci Rahmadini; Eva Latipah nusa (Insight School Academy, 2025)
Introduction to The Problem: The development of Graduate Learning Outcomes (CPL) in the Islamic Religious Education (PAI) curriculum often focuses more on academic competency than on their suitability to the developmental stage of students, even though students' cognitive, emotional, social, moral, and spiritual development influence their ability to understand and practice Islamic values. Purpose: This article aims to map the developmental stages of students in the CPL of the PAI curriculum and analyze its implications for curriculum development and learning. Design/methods/approach: The study used a qualitative approach with library research methods. Data were obtained through analysis of various scientific literature discussing the PAI curriculum, learning outcomes, and student developmental psychology, which were then examined using content analysis. Findings: The results indicate that CPL in the PAI curriculum needs to be formulated in stages according to the developmental characteristics of students at each level of education. In primary education, CPL is directed at establishing a foundation of faith, cultivating habits of worship, and strengthening morals through concrete experiences. In secondary education, CPL focuses on developing religious identity, critical thinking skills, social responsibility, and the ability to face the challenges of modern life based on Islamic values. These findings suggest that developmental stage mapping can serve as a basis for designing a more adaptive, humanistic, and learner-centered curriculum. Research limitations/implications: This research is limited to the use of library sources without empirical field testing. Practical implications: This study provides a conceptual contribution to the development of a developmental psychology-based Islamic Religious Education curriculum and serves as a reference for curriculum designers and educators in formulating a CPL that aligns with learner characteristics.